1996
DOI: 10.1159/000463748
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Modelling Based on a Structural Fragments Approach

Abstract: Today, predictive methods like Quantitative Structure-Activity Relationships (QSARs) play an important role in setting the priorities for risk assessment of chemicals. However, when a large number of compounds (>200) have to be considered, limitations arise on which physico-chemical variables to use. In this paper, a fast and easy way of chemically characterising compounds has been investigated. A QSAR is a regression model that relates the variation in the biological activity (y-matrix) within a homogenous se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Eriksson et al [14] demonstrated the use of PLS in combination with biodegradation data. The use of discriminant PLS on binary data has been described earlier by Lindgren et al [15]. The multivariate analyses were performed with SIMCA‐S version 6.0 [16] and the Matlab software package version 4.0 [17].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eriksson et al [14] demonstrated the use of PLS in combination with biodegradation data. The use of discriminant PLS on binary data has been described earlier by Lindgren et al [15]. The multivariate analyses were performed with SIMCA‐S version 6.0 [16] and the Matlab software package version 4.0 [17].…”
Section: Methodsmentioning
confidence: 99%
“…The power of the variables was equilibrated by scaling them to unit variance for the development of the main model [16]. In the study with fragment interactions, an intermediate type of scaling was applied as described by Lindgren et al [15]. This intermediate scaling (by square root of the standard deviation) equilibrated the power between the structural fragments, but not as far as to unity.…”
Section: Methodsmentioning
confidence: 99%
“…However, the use of expert judgment does not always lead to unequivocal answers; thus, more uniform ways of determining the domain are needed, such as the use of algorithms. Lindgren et al [87] proposed the use of partial least squares (PLS) to accomplish this, while Eriksson et al [106] proposed the use of cluster analysis for establishing that structurally related organic chemicals are represented in each set.…”
Section: General Principles For Developing Qsarsmentioning
confidence: 99%
“…Use of substructures as descriptors is the basis of the group contribution approach and is limited to chemicals which actually contain substructures used in the training set. Examples of group contribution approaches include calculation of log K ow [85], a biodegradation QSAR [86] and use in classification of chemicals [87]. One group contribution method for classifying chemicals is the Substructure‐based Computerized Chemical Selection Expert System (SuCCSES) [15–17,19].…”
Section: General Principles For Developing Qsarsmentioning
confidence: 99%
“…The 3D-QSAR of models of hydantoin-phenylpiperazine derivatives revealed a useful predictive information for the design of new selective ligands for 5-HT1A and α1 receptors [4]. A fast and easy way of chemical characterizing of the compounds has been described [5]. In this case, the QSAR was a regression model that related variation in the biological activity within a homogeneous series of the compounds (y matrix) to their structural properties (x matrix).…”
Section: Introductionmentioning
confidence: 99%